The Role of Language and its Analysis in James Joyce`s Dubliners within the Light of Cultural Materialism - Mojgan Gaeini; Mahnaz Soqandi; Fatemeh Sadat Basirizadeh (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
Language, Social identity and Religion are three major concerns of cultural studies. Language in literary texts plays a major role in constructing meaning and reflecting the author`s intention. Likewise religion as a cultural politics is a dominant factor in shaping mind as well in affecting the framework of literary text. Religion is one of the emerging issues in the modern era and forms the backbone of most literary works. Religion as a theme is seen to influence the operation of those who believe in it. It forms the functional framework that predetermines ones actions and behavior. Furthermore, social identity decides on the status of the social class and their material life situation.  Social identity relates to how we identify ourselves in relation to others according to what we have in common. All these issues are interrelated since they all cooperate and construct a social and cultural materiality. James Joyce could be placed among the most dominant cultural authors whose concern is the material life, social class, social identity and cultural crisis. As an outstanding author, Joyce is well known for his typical depiction, musical decoration as well as his sticking to proper cultural and social materials and issues such as religious matters. His major short story collection, Dubliners, revolves around the lifestyle of the Irish middle-class in Dublin around the late 1800s and early 1900s. This collection is decorated with violated norms and ritualistic behavior that are part of social constructs. Addressing social, religious and cultural issues, cultural materialists believe that “literature can serve as an agent of change”, since a culture`s hegemony is unstable. Raymond Williams views culture as a “productive process” that is, part of the means of production, and cultural materialism often identifies what he called “residual”, “emergent” and “oppositional” cultural elements. Seemingly, James Joyce`s Dubliners pertains to the notion of language, social identity and religion as cultural practices within the framework of cultural materialism. This study aims to clarify how James Joyce`s Dubliners reflects the notions of language, social identity and religion as cultural practices and how they construct social and cultural products within the framework of cultural materialism to show how James Joyce criticizes Irish culture at the beginning of the Twentieth century.